HUBUNGAN PENGETAHUAN DAN TINDAKAN BIDAN TERHADAP PROSES INVOLUSIO UTERI PADA IBU NIFAS DI KLINIK HAMIDAH - Nasution, Febriani; Lely, Lely (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
The success of health development plays an important role in improving the quality of human resources in every country. One indicator to assess the success of health development is from the high and low maternal mortality rate (MMR) in each country. According to the World Organization Helath (WHO) every minute a woman dies because of complications related to pregnancy, childbirth and childbirth. In other words 1400 women die every day or more than 500,000 women die every year due to pregnancy, childbirth and childbirth. This study aims to Analyze the Relationship of Knowledge and Actions of Midwives Against Uterine Involution Processes in Nifas Mothers at Hamidah Clinic in 2017. This study uses analytical research using a cross sectional time approach method that is a method of data retrieval carried out at a momentary time or a measurement with The population in this study were 35 midwives at the Hamidah Clinic using a questionnaire. From the results of the study obtained the majority of respondents aged 30-35 years as many as 18 respondents (51.4%), the majority of respondents D-III as many as 24 respondents (68.6%), the majority of working long respondents> 5 years as many as 22 respondents (62.9%), knowledgeable good as many as 27 respondents (77.1%), the majority of respondents performed 32 respondents (91.4%), while the p-value in the table was above 0.003 then (p) <0.05 then H0 was rejected so that there was a relationship between knowledge and actions of the Midwives on the Involvement Process Uteri on Mother Nifas at the Hamidah Clinic in 2017. It is expected to be able to improve the quality of health services by midwives the quality of health services for postpartum mothers towards involuntary uterine processes in the prevention of labor during IV IV bleeding.